Exclusive Breastfeeding Behavior and Clean Water Facilities with the Incidence of Diarrhea in Toddlers - Zulfiana, Yesvi; Nurul Fatmawati; Yopi Suryatim Pratiwi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Diarrhea is still the second cause of morbidity and mortality in children under five in Indonesia. Data from Basic Health Research (Riskesdas) in 2013 showed that the incidence of diarrhea in toddlers in Indonesia was 6.7%, a similar figure was also found in West Nusa Tenggara Province at 6.6%. Several factors are related to the incidence of diarrhea, namely exclusive breastfeeding and clean water facilities. This study aims to determine the relationship between exclusive breastfeeding and clean water facilities with the incidence of diarrhea in toddlers in Selagalas Village, the working area of the Cakranegara Community Health Center. The research design was cross sectional on 104 toddlers conducted in 3 selected environments in Selagalas Village. Data was collected by structured interviews using questionnaires and observation sheets. Data were analyzed bivariately with Stata SE 12.1. The results of this research were that 67 (64.42%) toddlers had experienced diarrhea. The variable related to the incidence of diarrhea is clean water facilities. There is no significant relationship between exclusive breastfeeding and the incidence of diarrhea. The importance of providing good and adequate clean water facilities, especially for mothers in caring for children.